Language Across Curriculum — Why Every Teacher should be a Language Teacher - Sangai, Sandhya (THE PRIMARY TEACHER, 2017)
Use of language is essential in the teaching–learning process. Learners assimilate new concepts through language. Ideas and content get conveyed and understood through language. Therefore, competent language skills facilitate learning in all subject areas. The Language Across Curriculum (LAC) approach emphasises how using Teaching Learning Materials (TLMs) available in different languages enhance the learners’ learning pace and quality of learning. So, all subject teachers must encourage correct use of language by the learners while reading, writing or discussing concepts, and in classroom processes related to their respective subjects. Input rich classroom and activity based teaching–learning process induce student–student and student–teacher interactions. Such an environment facilitates the use of different words by students. Also, the teachers can help the students choose appropriate words, according to the subject and context. This implies that content and language are interrelated, irrespective of the subject the learners are studying. Therefore, in order to promote centrality of language in learning, every teacher needs to be a language teacher.